2021
DOI: 10.1080/13510002.2021.1976568
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl cysteine ameliorates aortic fibrosis by promoting M2 macrophage polarization in aging mice

Abstract: Background: Vascular fibrosis is a universal phenomenon associated with aging, and oxidative stress plays an important role in the genesis of vascular damage in line with the aging process. However, whether antioxidants can ameliorate vascular fibrosis remains unclear. Objectives: The present study was to determine antioxidant N-acetylcysteine (NAC) could ameliorates aortic fibrosis in aging wild-type C57BL/6 mice. Methods : The aortas were harvested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“… 265 Similarly, NAC attenuates aging-related oxidative damage and neurodegeneration in rat brains by upregulating sirtuin-1 and downregulating several SASP factors (TNF-α, IL-1β, IL-6). 266 In addition, NAC extends the lifespan of mice 267 and ameliorates a series of aging-related diseases in rodents, such as AD, 268 , 269 aortic fibrosis, 270 immunosenescence, 271 oxidative stress and senescence in the lung, 272 bone loss in ovariectomized mice, 273 adipose tissue senescence and metabolic abnormalities, 243 and aging-related hearing loss. 274 …”
Section: Epigenetic Regulation Of Agingmentioning
confidence: 99%
“… 265 Similarly, NAC attenuates aging-related oxidative damage and neurodegeneration in rat brains by upregulating sirtuin-1 and downregulating several SASP factors (TNF-α, IL-1β, IL-6). 266 In addition, NAC extends the lifespan of mice 267 and ameliorates a series of aging-related diseases in rodents, such as AD, 268 , 269 aortic fibrosis, 270 immunosenescence, 271 oxidative stress and senescence in the lung, 272 bone loss in ovariectomized mice, 273 adipose tissue senescence and metabolic abnormalities, 243 and aging-related hearing loss. 274 …”
Section: Epigenetic Regulation Of Agingmentioning
confidence: 99%
“…The ESs of different doses of atropine groups all showed large treatment effects ( Supplementary Figure S2A ). In exploring the dose‒response relationship between atropine dose and ESs, we observed a significant linear correlation after excluding Zhu’s and Nucci’s studies which provided extreme findings (y = 1.08x + 0.86; r = 0.370, R 2 = 0.137; p = 0.013; Supplementary Figure S3A ) ( Zhu et al, 2021 ; Nucci et al, 2023 ). However, when we further exploring their nonlinear correlation, we found that the logarithmic equation has a better fitting effect (y = 0.23lnx+1.84, R 2 = 0.173, p = 0.005, Figure 3A ).…”
Section: Resultsmentioning
confidence: 88%
“…It is reported that FOXO1 participates in the regulation of cell senescence by regulating apoptosis, energy metabolism, DNA repair, etc (Salih & Brunet, 2008 ). The expression of FOXO1 was significantly decreased in the liver (Tomobe et al., 2013 ) and aorta (Zhu et al., 2021 ) of SAMP8 aging mice and normal aging mice, respectively. We next tested whether FOXO1 expression might change in macrophages during aging.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that FOXO1 participates in the regulation of cell senescence by regulating apoptosis, energy metabolism, DNA repair, etc (Salih & Brunet, 2008). The expression of FOXO1 was significantly decreased in the liver (Tomobe et al, 2013) and aorta (Zhu et al, 2021) Interestingly, no significant alteration of FOXO1 mRNA level was observed in the process (Figure 2e). We hypothesized that the changes of FOXO1 protein level were due to post-translational modifications, including phosphorylation and dephosphorylation (Kamoshita et al, 2022).…”
Section: Lta Prevents Macrophage Senescence By Inhibiting Foxo1 Downr...mentioning
confidence: 91%